Application of the OEE tool in an auto parts industry’s production line - Godoy, Hugo Carmaci Alves de; Santana, Caio Roberto Ferreira; Cazarotto, Tainá Gabriela da Silva; Barbosa, Luciano Wallace Goncalves (Revista Gestão da Produção Operações e Sistemas, 2020)
The aim of this paper is to work on lean manufacturing’s theory of tools in practice in a multinational auto parts industry responsible for the exhaust industry, located in state of São Paulo, Brazil. When use tools like OEE, TPM and Kaizen, it is possible to analyze the conditions of the equipment in the current scenario in production, proposing improvements such as professional maintenance planning, generating Kaizens, facilitating periodic activities (inspection, cleaning, lubrication and others) and training the employees to perform the autonomous maintenance, reducing the paras and faults of the equipment. was possible to optimize the OEE indicators: availability, performance and quality, resulting in a significantly better overall efficiency index.